Marco Polo : The Boy Who Explored China - Children's Historical Biographies - Baby Professor (United States Baby Professor, 2017)
Marco Polo was only a young boy when he joined his uncle and father in a journey to Asia. You can pretty much say that he was born to see the world. By reading his life story, your child might be encouraged to explore the world too. It will also open your child's eyes to the realizations of geographic and cultural differences. Meet Marco Polo today!
Keywords: Where We Are in Place and Time -- -Exploration; Biography -- Biography